STRATEGI PENINGKATAN EKONOMI LEMBAGA SOSIAL DENGAN MEMANFAATKAN APLIKASI PEMASARAN BERBASIS ANDROID (Studi kasus pada unit bisnis kidpreneuer di Yayasan AL MADINA Surabaya) - Saifuddin, Muchammad (JBT (JURNAL BISNIS dan TEKNOLOGI), 2020)
Digital Marketing which is all marketing efforts use electronic devices / internet,with a variety of marketing tactics and digital media where we can communicate with potential customers who spend time online. With the development of the times that prioritizes technology, author took the initiative to make optimal use of using marketing media effectively, namely by implementing Andoird Application to gain the profit of social foundation, the purposion of this research is making it easier for customers to find out online information about experience users in consuming products or brands, with the main goal to reach customers and can lead to profit.